Selection and seed production of vegetable crops – on an innovative path of development - A. V. Soldatenko; V. F. Pivovarov; O. N. Pyshnaya; L. K. Gurkina; E. V. Pinchuk (Овощи России, 2023)
The vegetable growing industry in Russia is the main component of crop production, the development of which determines the basis of life and food security. Being the most important and indispensable products of plant origin in the human diet, for a Russian, vegetables are in third place in importance after bread and potatoes. However, according to Rosstat, the level of selfsufficiency in vegetables and food melons in the country is 86,3%, which implies the need to increase their production. To improve the situation in the vegetable growing industry, an important place is given to the issues of improving selection and seed production, since the variety and high-quality seeds are the main elements of modern zonal crop cultivation technologies. At the Federal Scientific Center for Vegetable Growing, selection and seed production of vegetable crops is moving to an innovative development path, where, along with classical methods, modern methods are used: molecular marking according to the main economic characteristics, accelerated creation of homozygous lines using doubled haploid methods, plant immunity. In recent years, various methods of pre-sowing preparation of seeds have been developed to increase their viability and germination friendliness, to obtain even seedlings without harming the ecosystem. Based on the fundamental and priority applied research of previous years, in 2022, the creation of 17 varieties and hybrids of vegetable, melon and flower crops for all potential vegetable growing zones was completed. In order to provide the industry with pure-grade high-quality seed and increase the productivity of crops through the full use of the potential of the variety, the Federal Research Center for Vegetable Growing is constantly working in primary seed production. The developed zonal cultivation technologies will allow growing domestic products in various soil and climatic conditions of the country.